2021
DOI: 10.3389/fmicb.2021.589948
|View full text |Cite
|
Sign up to set email alerts
|

Trace Metal Contamination Impacts Predicted Functions More Than Structure of Marine Prokaryotic Biofilm Communities in an Anthropized Coastal Area

Abstract: Trace metal (TM) contamination in marine coastal areas is a worldwide threat for aquatic communities. However, little is known about the influence of a multi-chemical contamination on both marine biofilm communities’ structure and functioning. To determine how TM contamination potentially impacted microbial biofilms’ structure and their functions, polycarbonate (PC) plates were immerged in both surface and bottom of the seawater column, at five sites, along strong TM contamination gradients, in Toulon Bay. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 129 publications
(202 reference statements)
2
13
1
Order By: Relevance
“…In this study, for the sake of viability of encountered microbial communities, Cu was added in a range between 30 and 400 nM and between 6 and 60 nM when seawater was sampled from Pt12 (small bay of Toulon) and from Pt41p (large bay of Toulon), respectively, as Cu concentrations were shown to exhibit a decreasing gradient from the most enclosed part of the bay to the open waters (Coclet et al, 2018(Coclet et al, , 2021Layglon et al, 2020). In agreement with in-situ observations (Coclet et al, 2018(Coclet et al, , 2019Delpy et al, 2018)…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In this study, for the sake of viability of encountered microbial communities, Cu was added in a range between 30 and 400 nM and between 6 and 60 nM when seawater was sampled from Pt12 (small bay of Toulon) and from Pt41p (large bay of Toulon), respectively, as Cu concentrations were shown to exhibit a decreasing gradient from the most enclosed part of the bay to the open waters (Coclet et al, 2018(Coclet et al, , 2021Layglon et al, 2020). In agreement with in-situ observations (Coclet et al, 2018(Coclet et al, , 2019Delpy et al, 2018)…”
Section: Discussionsupporting
confidence: 78%
“…Potential bioaccumulation of TMs on MPs may also influence microbial biofilm diversity. Recently, biofilm formation on plastics panels did not appear to be mainly driven by seawater TMs content (Coclet et al, 2021, Catao et al, 2021a, despite strong evidence of the influence of Cu on other biofilm communities (Catao et al, 2019(Catao et al, , 2021b. However, in the Toulon-bay as well as in other coastal areas, a better understanding of the interactions of MPs-TMs is critical as MPs are most likely to be ingested by marine organisms and potentially transferred to high trophic levels though the trophic network (Andray, 2011).…”
Section: Seawater Copper Content Controls Biofilm Bioaccumulation and Microbial Community On Microplasticsmentioning
confidence: 99%
“…The reduction or absence of essential microorganisms in the nitrogen cycle will affect the nitrogen cycle chain and the transformation and removal of nitrogenous elements during bioremediation of eutrophic waters 54 . Other studies have shown that heavy metal contamination affects the abundance, composition and structure of microbial communities and disrupts replication processes by destroying microbial DNA 55 , 56 . The abundance of heavy metal susceptible microbes decreases as those resistant to these metal contaminants adapt and proliferate under chemical stress 49 .…”
Section: Discussionmentioning
confidence: 99%
“…However, 67.2% of the isolates studied in this work were sensitive to these herbicides, suggesting that changes in diversity in soil and water microbiota may occur in the presence of pesticides. Meanwhile, diversity molecular studies revealed that trace metal contamination in water environment have higher impacts on the functional profiles than on the structure of biofilm communities ( Coclet et al, 2021 ). The authors consider that biofilms are less impacted than planktonic communities to metal contamination due to a protection offered by the resistant species to all members in the community, and a wide range of specific mechanism of protection.…”
Section: Discussionmentioning
confidence: 99%